Perlindungan Hukum bagi Konsumen terhadap Pelaku Usaha yang Tidak Melakukan Pengumuman Hadiah Hasil Undian Via Media Massa - Larasati, Septifa Indah (UM Purwokerto Press, 2024)
In the digital era, announcing prize draw results through mass media has become commonplace. However, some business actors do not make such announcements, causing consumers not to know the results of the announced lottery. In this case, legal protection for consumers is crucial to guarantee their rights. Preventive legal protection Preventive legal protection includes providing clear and accurate information to consumers before participating in the lottery. This aims to save consumers from losses that may arise due to ignorance. Meanwhile, there is repressive legal protection, including legal action if the business actor does not publish the lucky draw results. In this case, consumers can sue business actors who do not announce the prize draw results via mass media. In this study, the author will discuss the legal protection of consumers against business actors who do not announce the prize draw results via the mass media. This research uses normative methods based on Law Number 8 of 1999 concerning Consumer Protection. The results of this study indicate that the legal protection of consumers is critical to guarantee their rights and avoid losses that may arise from a lack of understanding.